Treatment of foveal-involving tractional retinal detachments from proliferative diabetic retinopathy with intravitreal anti-VEGF therapy - Nihaal Mehta; G. Baker Hubbard (Retina, 2026)
Purpose: To report the outcomes of patients with fovea-off tractional retinal detachment (TRD) from proliferative diabetic retinopathy (PDR) treated with serial anti-VEGF therapy. Methods: We reviewed the medical records of patients with fovea-off TRD from PDR treated with serial anti-VEGF therapy. Outcome measures included visual acuity, foveal reattachment, need for vitrectomy, number of intravitreal injections, and average interval between injections. Results: 12 eyes of 10 patients were included. 75% of eyes (n = 9) had foveal reattachment with anti-VEGF therapy alone. The average time from TRD diagnosis to foveal reattachment was 15 months. Patient who experienced foveal reattachment (n = 9) received an average of 7 injections with an average injection interval of 2.3 months. At presentation, mean logMAR VA was 1.79 (Snellen visual acuity equivalent 20/1233). At 6 months, mean logMAR VA was 1.6 (20/790), and at 12 months, mean logMAR VA was 1.4 (20/466). At a last follow-up (mean 27.8 months), mean logMAR VA was to 1.36 (20/453) among all patients and 1.01 (20/204) among patients who had foveal reattachment. Conclusion: In this cohort of eyes treated with intravitreal anti-VEGF for fovea-off TRD from PDR retinopathy, we observed visual and anatomic stability, and, in some cases, improvement.